Effects of amlodipine and lacidipine on cardiac remodelling and renin production in salt-loaded stroke-prone hypertensive rats - Kyselovic, Jan (2001)
1. Calcium channel blockers (CCBs) are anti-hypertensive drugs that are usually considered to act mainly as vasodilators. We investigated the relation between the reduction of blood pressure evoked by two long-acting CCBs and their protective effect against cardiac and renal damage in salt-loaded stroke-prone spontaneously hypertensive rats (SHRSP). 2. SHRSP were exposed to high dietary salt intake (1% NaCl in drinking solution) from 8 to 14 weeks of age, with or without amlodipine or lacidipine at three dosage regimens producing similar effects on blood pressure. 3. The lowest dosages of both drugs had non-significant effects on blood pressure but inhibited the paradoxical increases in plasma renin activity (PRA) and in renin mRNA in kidney that were found in salt-loaded SHRSP. The lowest dosage of lacidipine (but not of amlodipine) restored the physiological downregulation of renin production by high salt and reduced left ventricular hypertrophy and mRNA levels of atrial natriuretic factor and transforming growth factor-β1. 4. The intermediate dosages reduced blood pressure and PRA in a comparable manner, but cardiac hypertrophy was more reduced by lacidipine than by amlodipine. 5. Although the highest doses exhibited a further action on blood pressure, they had no additional effect on cardiac hypertrophy, and they increased PRA and kidney levels of renin mRNA even more than in the absence of drug treatment. 6. We conclude that reduction of blood pressure is not the sole mechanism involved in the prevention of cardiac remodelling by CCBs, and that protection against kidney damage and excessive renin production by low and intermediate dosages of these drugs contributes to their beneficial cardiovascular effects.